2020
DOI: 10.1002/ijfe.1857
|View full text |Cite
|
Sign up to set email alerts
|

Development of Vietnamese stock market: Influence of domestic macroeconomic environment and regional markets

Abstract: This study has analysed the role of the domestic economic environment and regional markets (Thailand, Japan, Hong Kong and China) in explaining the dynamics of Vietnamese stock market. In so doing, we employed a time‐varying structural vector autoregression framework which accounts for time variations (in coefficients as well as in the variance–covariance matrix of innovations) on the data from July 2000 to December 2016. Our key findings suggested that the easing of monetary and credit conditions, stable and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 105 publications
0
16
0
Order By: Relevance
“…Second, the irrational factors increased their importance by explaining ETF portfolios during the European debt crisis. Our work is substantially different from that of Nasir et al (2018, 2021) and Thampanya et al (2020) in that it focuses on explaining rational and irrational factors that affect the two prominent strategies: value and momentum, similar to Asness et al (2013). Asness et al (2013) show that value and momentum anomalies work in different asset classes and financial markets worldwide.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Second, the irrational factors increased their importance by explaining ETF portfolios during the European debt crisis. Our work is substantially different from that of Nasir et al (2018, 2021) and Thampanya et al (2020) in that it focuses on explaining rational and irrational factors that affect the two prominent strategies: value and momentum, similar to Asness et al (2013). Asness et al (2013) show that value and momentum anomalies work in different asset classes and financial markets worldwide.…”
Section: Introductionmentioning
confidence: 94%
“…Second, it studies the goodness-of-fit of rational and irrational factors before, during and after a financial crisis. As Nasir et al (2018Nasir et al ( , 2021 reported, they analyze the influence of the domestic economic environment such as inflation, the exchange rate, interest rates and economic growth. They find that the global financial crisis is a gamechanger, and there is an intensive response during the period of financial turmoil.…”
Section: Introductionmentioning
confidence: 99%
“…If the expected return is higher than the average return, it is called investors' bullish expectations, and conversely, it is called investors' bearish expectations [7]. Even though the exact value of this average return expectation cannot be determined and is not considered, it does exist [8].…”
Section: Related Workmentioning
confidence: 99%
“…Vietnamese capital market fails to play the full role of a capital channel in the country since it remains young (Nasir, 2021). As a result, the banking system becomes the principal financing source for its firms (Chau et al, 2018).…”
Section: Vietnamese Capital Marketmentioning
confidence: 99%
“…Vietnam -a developing country with a strong presence of stateowned enterprises (SOEs), a less robust regulatory and legal environment, and rampant corruption -may be a typical case of countries of this type. Vietnamese capital market fails to play the full role of a capital channel in the country since it remains young (Nasir, 2021). As a result, the banking system becomes the principal financing source for its firms (Chau et al, 2018).…”
Section: Introductionmentioning
confidence: 99%